2009
DOI: 10.1111/j.1752-1688.2009.00309.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Nitrogen Loading to Ground Water and Assessing Vulnerability to Nitrate Contamination in a Large Karstic Springs Basin, Florida1

Abstract: A nitrogen (N) mass‐balance budget was developed to assess the sources of N affecting increasing ground‐water nitrate concentrations in the 960‐km2 karstic Ichetucknee Springs basin. This budget included direct measurements of N species in rainfall, ground water, and spring waters, along with estimates of N loading from fertilizers, septic tanks, animal wastes, and the land application of treated municipal wastewater and residual solids. Based on a range of N leaching estimates, N loads to ground water ranged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 53 publications
(75 reference statements)
5
26
0
Order By: Relevance
“…Upchurch et al, 2007), and springs discharge accounts for a large proportion of the N load to estuarine and coastal waters (Pittman et al, 1997). Despite the perceived vulnerability of the UFA to nutrient enrichment, river export accounts for only a moderate proportion of N inputs to North Florida landscapes, and considerable proportions of inputs remain unaccounted for (Katz et al, 2009). Landscape-scale mass balance generally suggests inorganic fertilizer as the primary source of N enrichment (Katz et al, 2009), but isotopic studies (that assumed negligible denitrification) have indicated a greater role of organic N from animal or human waste water (Katz et al, 2001).…”
Section: Study Systemmentioning
confidence: 99%
“…Upchurch et al, 2007), and springs discharge accounts for a large proportion of the N load to estuarine and coastal waters (Pittman et al, 1997). Despite the perceived vulnerability of the UFA to nutrient enrichment, river export accounts for only a moderate proportion of N inputs to North Florida landscapes, and considerable proportions of inputs remain unaccounted for (Katz et al, 2009). Landscape-scale mass balance generally suggests inorganic fertilizer as the primary source of N enrichment (Katz et al, 2009), but isotopic studies (that assumed negligible denitrification) have indicated a greater role of organic N from animal or human waste water (Katz et al, 2001).…”
Section: Study Systemmentioning
confidence: 99%
“…There have been only a few studies that have reported nutrient fluxes or loads for karst aquifers Currens, 2002;Panno and Kelly, 2004;Katz et al, 2009). Of these studies, only two, Boyer and Pasquarell (1996) and Panno and Kelly (2004), were conducted in recharge areas with agricultural land use intensity comparable to the Devils Icebox and Hunters Cave recharge areas.…”
Section: Nutrient Fluxmentioning
confidence: 99%
“…Highly elevated nitrogen levels have existed in the mid to lower main-stem Suwannee River Basin for some time (Pittman et al 1997;Katz and Bohlke 2000;Katz et al 2009). Springs have been shown to be primary vectors of this nitrogen.…”
Section: Other Watershed Variablesmentioning
confidence: 99%
“…The spring with the largest discharge (but not the highest nitrogen concentration) in that study contributed 550 kg of nitrates daily. Ammonia levels in springs are typically lower than U.S. Environmental Protection Agency Aquatic Life Ambient Water Quality Criteria, but ammonia is usually present in most groundwater wells and springs tested Katz et al 2009;EPA 2013). Ammonia is extremely toxic to larval and juvenile freshwater mussels (Wang et al 2007), and may persist longer in springs than in other systems because of low dissolved oxygen and eutrophic conditions limiting bacterial nitrification (Haag 2012).…”
Section: Other Watershed Variablesmentioning
confidence: 99%
See 1 more Smart Citation